1965
DOI: 10.1111/j.1423-0410.1965.tb01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptantigenic NVg Receptor in Mucoids from Mu/Mu Cells

Abstract: Résumé Les mucoïdes obtenus à partir des erythrocytes Mu/Mu qui dans leur forme originale (non traités) ne possèdent pas les récepteurs “N‐like” (Nvg) comme les mucoïdes des erythrocytes MU/MU, ont été trouvés comme ayant un effet inhibiteur sur la phythémagglutinine anti‐N obtenue à partir des semences de Vicia graminea si l'acide neuraminique était séparé à la suite d'un traitement par la neuraminidase (RDE). Zusammenfassung Mukoide von Mu/Mu‐Zellen, die im Gegensatz zu Mukoiden von MU/MU‐Zellen keine “N‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1969
1969
1981
1981

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…This is in contrast to the hypothesis of Uhlenbruck and Krüpe [44], who postulated in this case a maximal utilisation of the precursor by the N genes and subsequently the development of the maximum number of N receptors. Therefore we are left with the possibility, that the u gene also produces a special serological product and that the corresponding anti-u will be found one day.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…This is in contrast to the hypothesis of Uhlenbruck and Krüpe [44], who postulated in this case a maximal utilisation of the precursor by the N genes and subsequently the development of the maximum number of N receptors. Therefore we are left with the possibility, that the u gene also produces a special serological product and that the corresponding anti-u will be found one day.…”
contrasting
confidence: 52%
“…Another problem is that the MNSs active mucoids from red cells exhibit no U activity [Uhlenbruck and Krüpe,44] as should be expected on the basis of the proposed scheme in fig. 1.…”
mentioning
confidence: 99%
“…The removal of sialic acid has been proposed to change the conformation of the MN antigens, making them either inaccessible or unrecognizable to antibody (434,438,447). However, the oligosaccharide chains of sialidase-treated erythrocytes are exposed sufficiently to be recognized by anti-TF antibodies (448) and a variety of lectins (447), and to be substrates for either galactose oxidase (449), P-galactosidase (41 5 ) , or three different sialyltransferases (444). Thus removal of sialic acid probably does not sterically prevent access to the MN-specific region of glycophorin, although the molecular structure required for recognition of the MN antigens by most antibodies is clearly destroyed by sialidase.…”
Section: Pure Sialyltransferasesmentioning
confidence: 99%
“…This phenotype has been in terpreted by Prokop and Uhlenbruck [14] as due to complete conversion of precursor N to M (presumably by a hyperactive trans ferase). From this, Uhlenbruck and Kriipe [20] suggested that the M antigen of MU cells 'should have more M receptors'. Our data do not support this contention.…”
Section: Discussionmentioning
confidence: 99%